Changes in the proportion of regulatory T cell subpopulations during menstrual cycle and early pregnancy. (21st October 2022) - Okimura, Hiroyuki; Tanaka, Yukiko; Fujii, Maya; Shimura, Koki; Maeda, Eiko; Ito, Fumitake; Khan, Khaleque N.; Nakamura, Yoshitaka; Mori, Taisuke; Kitawaki, Jo
Abstract: Problem: Regulatory T cells (Tregs) play important roles in diseases occurring in women of reproductive age and pregnancy. Tregs are functionally heterogeneous and can be divided into activated Tregs (aTregs), resting Tregs (rTregs), and non‐suppressive Tregs (non‐Tregs). The purpose of this study is to investigate the change of Treg subpopulations during the menstrual cycle and early pregnancy. Method of study: Two groups of women were enrolled: healthy women aged 20 to 39 years with normal menstrual cycles and patients scheduled to undergo frozen‐thawed blastocyst transfer (FT‐BT) (subfertile women). Peripheral blood samples were collected at day 5 of the onset of menstruation (follicular phase), 0–2 days after luteinizing hormone (LH) surge (periovulatory phase), and 7–11 days after LH surge (luteal phase) from 20 healthy women. From 23 subfertile women, samples were collected at day 5 (the day of BT) and day 14 (the day of pregnancy testing) of progestogen administration during FT‐BT cycle and 9 weeks of gestation if the patient got pregnant. The proportion of total Treg and its subpopulations among CD4 + T cells was analyzed. Results: TTreg and aTreg proportion expanded during periovulatory phase ( p < .01) and after pregnancy ( p < .05 for tTreg and p < .01 for aTreg). rTreg proportion was significantly high during periovulatory phase ( p < .01) and during luteal phase ( p < .01). Non‐Tregs showed no significant change. Conclusions: RTregs and aTregs, especially in luteal phase and after getting pregnant, showed significant changes and may play important roles in women of reproductive age.